1990
DOI: 10.1111/j.1469-8749.1990.tb08430.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Conditions Of Adolescents With Myelomeningocele

Abstract: SUMMARY Twenty six adolescents with myelomeningocele have been followed from birth: they comprise the whole population born with myelomeningocele between 1964 and 1967 in one Swedish medical district. 18 have severe physical handicaps, and although there are equal numbers of males and females, more females have severe handicaps. 22 of the 26 have been educated in normal schools (19 in normal classes), but learning difficulties are common. Three other adolescents are mildly mentally retarded and one is severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…Dating occurs with a significantly lower frequency among adolescents with a physical disability [3,11]. However, findings are not consistent about the degree to which adolescents with physical disabilities engage in sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dating occurs with a significantly lower frequency among adolescents with a physical disability [3,11]. However, findings are not consistent about the degree to which adolescents with physical disabilities engage in sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that adolescents with physical disabilities are poor informed about general sexual knowledge [3,11,15]. It is suggested that the lack of knowledge has to do with the fact that these adolescents are often isolated from others of their age and that as a consequence this might lead to a lack of opportunities to learn about (their) sexuality or to engage in social activities or sexual experiences [15].…”
Section: Introductionmentioning
confidence: 99%
“…3 However, perceived health has only rarely been studied in this group; most studies have focused on physical independence and living conditions, 4,5 social relationships or vocation, 4-9 feelings of competence, 5, 6, 10 behavioural problems, 8,11,12 or well-being. 4 Parkin et al 13 developed a specific HRQL scale for children and adolescents with spina bifida. This scale consists of 47 items in 10 domains, including physical independence, recreation, emotions, medical care, and finances.…”
mentioning
confidence: 99%
“…Therefore, studies have been performed in order to demonstrate QoL and functional status in SB. In their study on 26 children with myelomeningocele, Börjeson and Lagergren (18) found that 23 of them were able to perform cleaning, dressing, and bathing independently. Buran et al (19) assessed 66 adolescents with SB using WeeFIM and reported that most of them were independent in the areas of eating, cleaning, dressing, mobility, and transfers.…”
Section: Discussionmentioning
confidence: 99%